Konsep Kepribadian Guru: Konsekwensi Empirik Kualitas Pendidikan Indonesia - Ahmad, Nuril (MADINAH, 2015)
Teachers are professions that experience ups and downs in the world of professional arts. Even if the teacher was considered a sacred profession, it boasted to be seen when proudly a teacher, but is now presumed to be a marginal profession. This is evident from the many generations of successors who are a little aspiring to a teacher. They tend to make doctors, engineers, pilots a choice of the profession in the future. There are a variety of reasons put forward due to their unwillingness, but it is clear that welfare is the first place for a person not to choose a teacher as a profession.